Association of Comorbidities and Levels of Depression among Pre-elderly with HIV in DKI Jakarta - Ni Wayan Mutiara Suasti Suta; Surilena Surilena; Dharmady Agus; Eva Suryani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: The presence of comorbidities in pre-elderly with HIV can worsen the disease symptoms, and disabilities, and lead to the emergence of depressive symptoms. Depression in the pre-elderly can cause a decrease in quality of life and failure to achieve successful aging. This study aims to determine the association between comorbidities and the level of depression among pre-elderly with HIV. Method: This is an observational analytic study with a cross-sectional method using a characteristic questionnaire (age, gender, education level, occupation, economic status, and marital status), comorbidities questionnaire, and PHQ-9 questionnaire. This study used convenience sampling and obtained 161 pre-elderly respondents (45—59 years) with HIV among pre-elderly with HIV in DKI Jakarta. The data analysis was done using the Fisher Exact test using STATA. Result: There were 161 pre-elderly with HIV, 74,16% were men, 55,28% were in Senior High School, 72,67% were working, 76,4% had low economic status, and 44,72% were not married. A total of 59,85% have one comorbid condition. There were 81,37% with physical comorbidities, including 40,82% arthritis, 38,27% hypertension, 6,63% diabetes mellitus, and 51,55% with depression including 27,95% mild depression, 16,15% moderate depression, 5,59% moderate severe depression, and 1,86% severe depression. No significant association was found between comorbidities and the levels of depression among pre-elderly with HIV (p=0,341). The presence of physical comorbidities in pre-elderly with HIV can affect the disease progression and its treatment. However, in this study, There is no significant association between comorbidities and the levels of depression among pre-elderly with HIV in DKI Jakarta. It is recommended that further research be conducted using in-depth interviews to explore the relationship between physical comorbidities and depression in pre-elderly with HIV.